Analisa Performansi Pengendali Hybrid Sliding Mode (DSM) dan Sliding Mode dengan Permukaan Luncur PID Pada Proses CSTR - Dian Mursyitah; ahmad Faizal; Ewi Ismaredah (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2019)
This study proposes a comparative analysis of controls for controlling levels and concentrations in the CSTR process. The controller designed to analyze its performance is sliding mode. Comparison of controller performance analysis is shown by differences in sliding surfaces. The design starts with designing the dynamic sliding surface and the PID on the sliding mode controller. Then, the two controllers are combined. Analysis is done by comparing the performance of the three controllers in controlling the level and concentration of the CSTR system. The simulation results show hybrid controllers are able to reach the set point faster than the other two controllers, this is proved by the value of ts = 0.016 s for the level and ts = 0.072 s for concentration. However, sliding mode controller with PID sliding surface is a controller that is able to reduce the largest steady state error compared to the other two controllers, with the value E_ss = 0.